The Contribution of Archives Management in the Performance of Local Government Central Registry, Rwanda. - Judith, Uwamwezi (Kabale University, 2019)
A Research Dissertation Submitted to the Faculty of Arts and Social Sciences in Partial Fulfillment of the Award of a Bachelor’s Degree in Library and Information Science of Kabale University